2020
DOI: 10.1097/sla.0000000000003917
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Symptoms After Esophageal Resection (LASER)

Abstract: Objective: To identify the most prevalent symptoms and those with greatest impact upon health-related quality of life (HRQOL) among esophageal cancer survivors. Background: Long-term symptom burden after esophagectomy, and associations with HRQOL, are poorly understood.Patients and Methods: Between 2010 and 2016, patients from 20 European Centers who underwent esophageal cancer surgery, and were disease-free at least 1 year postoperatively were asked to complete LASER, EORTC-QLQ-C30, and QLQ-OG25 questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 24 publications
2
55
1
Order By: Relevance
“…A recent prospective multicenter study showed that the majority of patients have functional complaints that last up to more than 1 year after an esophagectomy. 29 The authors found a relation between the absence of 30-day complications and HR-QoL, with an increased physical, social, role functioning, and global health status in the group without complications.…”
Section: Discussionmentioning
confidence: 92%
“…A recent prospective multicenter study showed that the majority of patients have functional complaints that last up to more than 1 year after an esophagectomy. 29 The authors found a relation between the absence of 30-day complications and HR-QoL, with an increased physical, social, role functioning, and global health status in the group without complications.…”
Section: Discussionmentioning
confidence: 92%
“…The LASER study is a prospective European multicenter cross-sectional study, which aimed to identify symptoms with the highest incidence and the greatest impact on HRQL in disease-free patients following an esophagectomy for esophageal or gastro-esophageal junction cancer. [22] The primary study outcomes of the LASER study have been published before. [22] Ethical approval to use the LASER study dataset for side studies were gained by each participating centre during the original LASER study, and written informed consent was signed by all participants to use their data in retrospective studies.…”
Section: The Lasting Symptoms After Esophageal Resection (Laser) Stud...mentioning
confidence: 99%
“…[20,21] Therefore the primary aim of this study was to examine whether long-term HRQL differs with the occurrence and severity of postoperative complications in a European multicenter prospective dataset J o u r n a l P r e -p r o o f of esophagectomy patients (LASER study). [22] We hypothesized that the severity of postoperative complications are proportionally negatively associated with long-term HRQL: patients with severe complications are likely to have significantly worse long-term HRQL compared to patients with no or minor postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…NCD users usually enter data 90 days after surgery to provide data on 90-day mortality, and weight loss often occurs at the time of data entry, especially after esophagectomy, gastrectomy, and pancreaticoduodenectomy. [15][16][17] The concordance rates for data on wound class (92.7%), ASA class (87.2%), and anesthesia technique (90.5%) were also <95%. To reduce the number of disagreements, we have added several alarms on the NCD web input form from 2016.…”
Section: 4% In 2005-2008)mentioning
confidence: 95%